Effect of Particle Size and Temperature on Pyrolysis of Palm Kernel Shell - Zaman, Khairunnisa Kamarul; Balasundram, Vekes; Ibrahim, Norazana; Samsudin, Mohammad Dinie Muhaimin; Kasmani, Rafiziana Md.; Abd Hamid, Mohd. Kamaruddin; Hasbullah, Hasrinah (International Journal of Engineering and Technology, 2018)
Pyrolysis is a viable solution to curb the issue of growing lignocellulosic waste in the world through conversion to potential biofuel and bio-based chemicals. This study focused on the effect of biomass particle size on the feedstock characterisation, biomass ash content, thermal behaviour and pyrolysis products yield. The particle size ranges studied were <0.355, 0.355 to 0.710. 0.710 to 1.00 and 1.00 to 2.00 mm. Thermal behaviour was analysed using thermogravimetric analyser, and pyrolysis experiments were conducted in a fixed-bed pyrolyzer. TGA results show smaller particle size maximum temperature shifted to a lower temperature. From ashing, the results indicated that ash content is the highest at the smallest particle size, <0.355mm (2.8 wt.%). The gaseous yield was the highest in dpA (<0.355 mm) at a temperature of 600°C. The highest pyrolysis oil yield (50.1 wt.%) occurred at 400°C from dpA (<0.355mm). The highest char yield (33.70 wt.%) occurred at 400°C obtained from the largest particle size, dpD (1-2mm).